Acceptability of Implantable Continuous Glucose Monitoring Sensor. (May 2018) - Barnard, Katharine D.; Kropff, Jort; Choudhary, Pratik; Neupane, Sankalpa; Bain, Stephen C.; Kapitza, Christoph; Forst, Thomas; Link, Manuela; Mdingi, Colleen; DeVries, J. Hans
Background: Real-time continuous glucose monitoring is associated with significant benefits for diabetes management. Implantable sensors could overcome some challenges reportedly associated with device visibility, psychosocial functioning and sensor durability. Methods: A psychosocial assessment was conducted to determine acceptability and impact of an implantable continuous glucose monitoring (CGM) sensor as part of the PRECISE trial. Questionnaires were administered to participants comprising the Diabetes Distress Scale, the CGM impact scale, and bespoke device satisfaction. Results: Fifty-one participants across the United Kingdom (n = 10) and Germany (n = 41) completed the questionnaires. Of these, 90% had T1D, 50% followed an insulin pump therapy regimen, and 45% of the participants were previous CGM users. CGM Impact Scale results show 86% (n = 44) of participants reported feeling better (14% neutral) about their diabetes control with 90% CGM naïve participants and 81% previous CGM users reporting increased confidence about their diabetes management. Furthermore, 73% (n = 37) felt more safe (27% neutral) while sleeping and 78% (n = 39) more confident (22% neutral) about avoiding serious hypoglycemia. Responses correspond with an average improvement in HbA1c from 7.51 to 7.05 ( P < .0001) over the 90 days use of the CGM. Overall, the system was rated highly on ease of use, convenience and comfort. 84% would choose to be inserted again with 93% of CGM naïve participants (86% previous CGM users) reporting minimized burden of diabetes. Conclusions: Implantable CGM devices are acceptable to users and are evaluated favorably. The considerable majority of participants (93% of first time users and 77% previous CGM users) would like to continue using the system to help manage their diabetes more effectively.